KOLABORATIF GOVERNANCE DALAM PENGELOLAAN KALURAHAN WISATA BUDAYA DAN EKONOMI KREATIF DI PURBAYAN, YOGYAKARTA - Susak, Rizka Devi; Rahmawati, Agustina (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This research discusses the implementation of Collaborative Governance in cultural and creative economic management in Purbayan, Yogyakarta using a multidisciplinary approach in realizing Sustainable Development. This research explores the form of cooperation or collaboration between the government, the community, and the creative industry to design a harmonized plan to encourage economic progress and cultural heritage preservation. The results show that a collaborative governance approach involving various sectors has a positive impact on aspects of the SDGs. The implementation of this model will not only improve the economic welfare of the community and creative industry players, but also strengthen local cultural capacity and increase community participation. In this research, it is explored how this interdisciplinary cooperation model can be sustained and whether this model has made a significant contribution in achieving SDGs goals such as poverty alleviation, inclusive economic growth, cultural preservation, and others. Through this holistic approach, it is hoped that Purbayan can become an example of success in integrating collaboration between the government, community, and private sector to improve the welfare and sustainability of the local economy.